2021
DOI: 10.1186/s40168-020-00966-y
|View full text |Cite
|
Sign up to set email alerts
|

Dicer-like proteins influence Arabidopsis root microbiota independent of RNA-directed DNA methylation

Abstract: Background Plants are naturally associated with root microbiota, which are microbial communities influential to host fitness. Thus, it is important to understand how plants control root microbiota. Epigenetic factors regulate the readouts of genetic information and consequently many essential biological processes. However, it has been elusive whether RNA-directed DNA methylation (RdDM) affects root microbiota assembly. Results By applying 16S rRNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 95 publications
0
16
0
Order By: Relevance
“…For instance, mutant dcl234 , an Arabidopsis triple mutant with defects in the RNA‐directed DNA methylation (RdDM) pathway, had a reduced abundance of Aeromonadaceae and Pseudomonadaceae and an increased abundance of other families in the root microbial community. However, this regulation was independent of RdDM, and may have been caused by a series of modulations of cell‐wall components, root exudates, and plant defenses (Kaushal et al, 2021). Comparing the root microbiome of three rice mutants defective in histone methylation, researchers found that histone methylation may have modulated the microbiome structure and composition by affecting the abundance of hub species (Lv et al, 2021).…”
Section: Main Factors Affecting the Root Microbiotamentioning
confidence: 99%
“…For instance, mutant dcl234 , an Arabidopsis triple mutant with defects in the RNA‐directed DNA methylation (RdDM) pathway, had a reduced abundance of Aeromonadaceae and Pseudomonadaceae and an increased abundance of other families in the root microbial community. However, this regulation was independent of RdDM, and may have been caused by a series of modulations of cell‐wall components, root exudates, and plant defenses (Kaushal et al, 2021). Comparing the root microbiome of three rice mutants defective in histone methylation, researchers found that histone methylation may have modulated the microbiome structure and composition by affecting the abundance of hub species (Lv et al, 2021).…”
Section: Main Factors Affecting the Root Microbiotamentioning
confidence: 99%
“…Microbiome samples were collected based on previous publications ( Lareen et al, 2016 ; Kudjordjie et al, 2019 ; Kaushal et al, 2021 ). Briefly: the rhizosphere substrates were collected from maize and tiger lily grown on Cambrian, Ordovician, and Silurian soil in Xiangxi prefecture, Hunan province, China.…”
Section: Methodsmentioning
confidence: 99%
“…DNA sample preparation and 16S rRNA gene sequencing were performed as previously described ( Kaushal et al, 2021 ), with minor modifications. Briefly, total DNA was extracted with the FastDNA ® SPIN Kit for Soil (MP Biomedicals, Solon, OH, USA) following the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Phytohormone changes in plant physiology produce alterations in PRE composition and, therefore, in microbial communities, as reported for jasmonic acid (JA) [ 33 , 34 ]. Furthermore, using a triple mutant in Dicer-like genes involved in small RNAs biogenesis, Kaushal et al [ 87 ] found an altered PRE composition, which can partially explain the observed modifications in the root microbial community.…”
Section: Arabidopsis Features That Shape Its Microbial Communitiesmentioning
confidence: 99%